Epidemiology of work-related burn injuries presenting to burn centres in Australia and New Zealand. Issue 2 (March 2019) - McInnes, Judith A.; Cleland, Heather; Tracy, Lincoln M.; Darton, Anne; Wood, Fiona M.; Perrett, Tracey; Gabbe, Belinda J.
Highlights: 17% of serious adult burns in Australia and New Zealand, 2009–16 were work-related. Work-related cases were predominantly male, and aged less than 35 years. Causes of work-related and non-work-related burns differed markedly. Most work-related burns were caused by flame, scald or chemicals. Proportions of electrical burns were seven times greater for work-related cases. Abstract: Background: Burn injuries to workers can have a devastating impact, however knowledge of the epidemiology of work-related burn injuries in Australia and New Zealand is limited. Purpose: To describe epidemiological characteristics of work-related burn injuries in Australia and New Zealand, and to compare these with non-work-related burns. Methods: Adult burn injury data, 2009–2016, were extracted from the Burns Registry of Australia and New Zealand. Descriptive statistics were used to describe demographic, injury, management and outcome characteristics. Differences between work-related and non-work-related injuries were assessed using Chi-square and Wilcoxon rank-sum tests. Results: Of 10, 574 adult patients treated in burn centres in Australia and New Zealand, 2009–2016, 17% had work-related burns. Most work-related cases were male (85%), less than 35 years old (53%), and had sustained flame (33%), scald (30%) or chemicals (17%) burns. Proportions of chemical, scald and electrical burns were greater for work-related than for non-work-related burns, with this being most marked for chemical and electrical burns (17% vs. 3% and 7% vs. 1%, respectively). Conclusions: Almost one in five cases of working-aged people admitted to Australian and New Zealand burns centres was work-related. Through identification of vulnerable groups, this study informs policy and strategies to minimise occupational burn risk.